MRI-detected subclinical joint inflammation is associated with radiographic progression. Issue 11 (29th July 2014) - Krabben, A; Stomp, W; van Nies, J A B; Huizinga, T W J; van der Heijde, D; Bloem, J L; Reijnierse, M; van der Helm-van Mil, A H M
Abstract : Background: We recently demonstrated that MRI inflammation is prevalent in clinically non-swollen joints of early arthritis patients. In this study, we assessed the relevance of this subclinical inflammation with regard to radiographic progression. Methods: 1130 joints (unilateral metacarpophalangeal 2–5, wrist and metatarsophalangeal 1–5) of 113 early arthritis patients underwent clinical examination and 1.5 T MRI at baseline, and radiographs at baseline and 1 year. Two readers scored the MRIs for synovitis, bone marrow oedema (BME) and tenosynovitis according to Rheumatoid Arthritis (RA) Magnetic Resonance Imaging (MRI) Scoring System (RAMRIS). Radiographic progression over 1 year was determined using the Sharp–van der Heijde scoring method. Results: On patient level, BME, synovitis and tenosynovitis were associated with radiographic progression, independent of known risk factors (p=0.003, 0.001 and 0.011, respectively). Of all non-swollen joints (n=932), 232 joints (26%) had subclinical inflammation (≥1 MRI-inflammation feature present). These joints were distributed among 91% of patients. Radiographic progression was present in 4% of non-swollen joints with subclinical inflammation compared to 1% of non-swollen joints without subclinical inflammation (relative risks (RR) 3.5, 95% CI 1.3 to 9.6). Similar observations were done for BME (RR5.3, 95% CI 2.0 to 14.0), synovitis (RR3.4, 95% CI 1.2 to 9.3) and tenosynovitis (RR3.0, 95% CI 0.7 to 12.7) separately. Conclusions: Radiographic progression was infrequent, but joints with subclinical inflammation had an increased risk of radiographic progression within year 1. This demonstrates the relevance of MRI-detected subclinical inflammation.